Planar and Nanostructured n‐Si/Metal‐Oxide/WO3/BiVO4 Monolithic Tandem Devices for Unassisted Solar Water Splitting. Issue 2 (23rd December 2020) - Ahmet, Ibbi Y.; Berglund, Sean; Chemseddine, Abdelkrim; Bogdanoff, Peter; Präg, Raphael F.; Abdi, Fatwa F.; van de Krol, Roel
Abstract : Solar Water Splitting In article number 2000037, Ibbi Y. Ahmet, Roel van de Krol, and co‐workers fabricate a tandem monolithic nanostructured dual photoanode consisting of n‐Si/SiOx /TiO2 /WO3 /BiVO4 /Fe(Ni)OOH using a scalable chemical deposition processes. The interfacial layers between the n‐Si and BiVO4 dual absorber layers are crucial to enhance the photocurrent density and overall photovoltage, which subsequently enables unassisted solar water splitting.